2021
DOI: 10.1111/scd.12591
|View full text |Cite
|
Sign up to set email alerts
|

Is Sjogren's syndrome a risk factor/contraindication for dental implants? An umbrella review

Abstract: Introduction There have been concerns that longstanding oral dryness secondary to Sjogren's syndrome may increase the risk of failure of dental implants. Aims The aim of the present study was to determine the level of methodological quality of systematic reviews that evaluated the effectiveness of dental implants in patients diagnosed with Sjogren's syndrome. Methods and results Databases of PubMed/Medline, LILACS, Science Direct and Dare Cochrane to October 2020 were evaluated. A total of 833 articles were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…To date, no prospective clinical trials have been published in which the success of implant supported overdentures in SjD patients was investigated prospectively and compared to subjects without SjD. Only retrospective studies and case series reported on the use of dental implants in edentulous patients with SjD, often with favourable outcomes comparable to healthy subjects (15)(16)(17)(18)(19), but occasionally with less favourable outcomes such as an above average loss of implants (20,21). Therefore, this study aims to prospectively investigate patient-reported outcome measures and the clinical performance of implant supported overdentures in edentulous SjD patients compared to subjects without SjD.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no prospective clinical trials have been published in which the success of implant supported overdentures in SjD patients was investigated prospectively and compared to subjects without SjD. Only retrospective studies and case series reported on the use of dental implants in edentulous patients with SjD, often with favourable outcomes comparable to healthy subjects (15)(16)(17)(18)(19), but occasionally with less favourable outcomes such as an above average loss of implants (20,21). Therefore, this study aims to prospectively investigate patient-reported outcome measures and the clinical performance of implant supported overdentures in edentulous SjD patients compared to subjects without SjD.…”
Section: Introductionmentioning
confidence: 99%
“…136 • Autoimmune/inflammatory/rheumatoid/skin diseases, 128 especially Sjogren's syndrome. 137,138 • Genetics/epigenetics. 116,[139][140][141] • HIV-1.…”
Section: Other Potentially Systemic Driversmentioning
confidence: 99%
“…To date, no prospective clinical trials have been published in which the success and survival of implants in patients with SS were investigated and compared to healthy subjects. Only retrospective studies and case series reported on the use of dental implants in patients with SS, often with favorable outcomes (Albrecht et al, 2016 ; Almeida et al, 2017 ; Barros et al, Barros et al, 2021 ; Chrcanovic et al, 2019 ; Korfage et al, 2016 ), but also with less favorable outcomes such as an above average loss of implants (Isidor et al, 1999 ; Payne et al, 1997 ). Therefore, this study aims to prospectively investigate the clinical performance and patient‐reported outcomes of dental implants in dentate patients with SS compared to subjects without SS up to 18 months after placement of the suprastructure.…”
Section: Introductionmentioning
confidence: 99%